1998
DOI: 10.1159/000029820
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nitrate: Antimicrobial Activity Related to Cytotoxicity in Cultured Human Fibroblasts

Abstract: The aims of this study were to ascertain whether silver nitrate (AgNO3) concentrations below those used in clinical practice inhibit bacterial growth, and in parallel study the cytotoxic effects on human fibroblasts. The cytoprotective effects of fetal calf serum (FCS) were also evaluated. The cytotoxic effects of eight different silver nitrate concentrations were determined by assessing mitochondrial activity of viable cells capable of cleaving tetrazolium salts. Antimicrobial activity of AgNO Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 24 publications
1
58
0
Order By: Relevance
“…We used three wells for all combinations of C2DA with antibiotics, and four wells for biocompatibility tests. In studies of antimicrobial effects on toxicity, 50% to 100% reductions in viability were observed [5,11,24]. Given the approximate SD of 500 cells per well, we could detect a difference of 1500 cells per well (around 20% of control values) with 80% power using ANOVA analysis.…”
Section: Methodsmentioning
confidence: 94%
“…We used three wells for all combinations of C2DA with antibiotics, and four wells for biocompatibility tests. In studies of antimicrobial effects on toxicity, 50% to 100% reductions in viability were observed [5,11,24]. Given the approximate SD of 500 cells per well, we could detect a difference of 1500 cells per well (around 20% of control values) with 80% power using ANOVA analysis.…”
Section: Methodsmentioning
confidence: 94%
“…To address this, some recent studies have tried to implement two-dimensional, monolayer coculture systems of cells and bacteria to test antimicrobial agents that can be added to the culture medium. [27][28][29][30] To date, there is no published method on evaluating antimicrobial dressings in coculture systems. Therefore, we designed a novel 3D coculture system to assess the cytotoxicity and antimicrobial properties of antimicrobial scaffolds/wound dressings in one experiment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our study (Bacakova et al, 2008b) an LB medium, containing bacto-tryptone (10 g/l), bacto-yeast extract (5g/l) and NaCl (10g/l) in H 2 O was used. It has been reported that the serum supplement of the culture media has protective effects against the cytotoxic action of silver (Hidalgo et al, 1998;Sun et al, 2006). Thus, the promising results obtained in both studies by Bacakova et al (2008b) and Vasilev et al (2010) should be further investigated, particularly using the culture media of the same chemical composition for both mammalian and bacterial cells.…”
Section: Hydrocarbon Plasma Polymersmentioning
confidence: 94%